Creating Lasting Change through Collaboration and Engagement - Marilu Goodyear; Jenny Mehmedovic (Academic Chairpersons Conference Proceedings, 2015)
Have you experienced difficulty moving a critical change forward and building the buy-in you need? Come learn how to get everyone moving forward with you. Real-life examples from a recent curriculum redesign project will be discussed and participants will apply organizational change concepts to a change initiative of their own.
Keywords: Change; Curriculum; Resistance; Stakeholders; Collaboration